2020
DOI: 10.1371/journal.pone.0228167
|View full text |Cite
|
Sign up to set email alerts
|

Towards an ontology of cognitive processes and their neural substrates: A structural equation modeling approach

Abstract: A key challenge in the field of cognitive neuroscience is to identify discriminable cognitive functions, and then map these functions to brain activity. In the current study, we set out to explore the relationships between performance arising from different cognitive tasks thought to tap different domains of cognition, and then to test whether these distinct latent cognitive abilities also are subserved by corresponding "latent" brain substrates. To this end, we tested a large sample of adults under the age of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…The entorhinal cortex is concerning because it is commonly influenced by most dementing conditions, and thus the lack of results in the entorhinal cortex in particular is unusual. One interpretation of this finding may be that these regions are commonly reduced across the WTC responder population, but may not be sufficient to cause cognitive symptoms on their own 62 . Results comparing CTX in cognitively unimpaired WTC responders with published normative data from 2,799 cognitively normal adults 27 identified substantial reductions in the entorhinal cortex and across the temporal lobe despite revealing thicker cortices on average across many other regions; results may suggest that cognitively unimpaired WTC responders also have some abnormalities in this region of the brain.…”
Section: Discussionmentioning
confidence: 98%
“…The entorhinal cortex is concerning because it is commonly influenced by most dementing conditions, and thus the lack of results in the entorhinal cortex in particular is unusual. One interpretation of this finding may be that these regions are commonly reduced across the WTC responder population, but may not be sufficient to cause cognitive symptoms on their own 62 . Results comparing CTX in cognitively unimpaired WTC responders with published normative data from 2,799 cognitively normal adults 27 identified substantial reductions in the entorhinal cortex and across the temporal lobe despite revealing thicker cortices on average across many other regions; results may suggest that cognitively unimpaired WTC responders also have some abnormalities in this region of the brain.…”
Section: Discussionmentioning
confidence: 98%
“…Cognitive functions can be viewed as the behavioral outcome of collaborative processing of sensory information by distributed but interconnected neural systems ( Mesulam 1998 ). Based on psychometric theory and supported by neuroscientific evidence of specialized neural networks ( Eich et al. 2020 ), cognitive functions can be subdivided into domains such as processing speed, reasoning, and memory, to name but a few ( McGrew 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, future research needs to determine conclusive evidence for executive, language, social cognition and memory functions across the ALS-FTSD. Given that the architecture of cognition remains a matter of debate [52][53][54] and that atrophy is widespread, 18 future studies should direct their attention towards cognitive networks to investigate the interrelationships between cognitive functions in ALS-FTSD. Establishing cognitive networks may reveal structures underlying these vulnerabilities.…”
Section: Discussionmentioning
confidence: 99%
“…This absence is likely because neuroscience overall still struggles to map cognitive functions onto brain areas 53 and to establish the architecture of cognitive functions overall. Factor analyses have suggested that memory and reasoning could be one domain 54 and that verbal fluency might be a language function rather than an executive one as it relates to both domains 52 . This necessitates future network analyses, to see if ALS‐FTSD patients and healthy persons differ in their cognitive architecture.…”
Section: Discussionmentioning
confidence: 99%